The first human case report of molecularly confirmed co-infection of Brucella melitensis and Coxiella burnetii: A case report - Onjira Mangkalamanee; Suwatchareeporn Rotcheewaphan; Pawat Phuensan; Teerada Ponpinit; Thiravat Hemachudha; Pattama Torvorapanit (Heliyon, 2024)
Co-infection with Brucella melitensis and Coxiella burnetii has been rarely reported. To date, there are only two co-infection case reports from Croatia and China which diagnosed the infections mainly through the use of serological tests. In this report, we present the first case of molecularly confirmed B. melitensis bacteremia and C. burnetii spondylodiscitis co-infection in a goat dairy farmer who presented with lumbosacral spondylodiscitis and bilateral psoas abscesses. From the blood culture, B. melitensis was identified by using 16S rRNA gene sequencing and specific PCR. Lumbar bone tissue was found to be positive for C. burnetii using multiplex real-time PCR and was confirmed with a positive result from conventional PCR which detected the infection through the identification of the IS1111 gene. The patient's condition improved after decompressive laminectomy was performed and administration of antibiotics regimen: intravenous gentamicin, oral rifampicin, and oral doxycycline. From our case, it is important to raise awareness of this underreported co-infection with multiple zoonotic diseases, especially Q fever and brucellosis, which share the same exposure risk. Moreover, we also emphasize the use of advanced molecular techniques to improve the diagnostic efficiency and reduce the use of time-consuming procedures among patients who are continuously exposed to such risk factors in areas with high seroprevalence of these zoonotic diseases.